Communication: Innovation & Quality - Túñez-López, Miguel; Martínez-Fernández, Valentín-Alejandro.; López-García, Xosé.; Rúas-Araújo, Xosé.; Campos-Freire, Francisco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores the disruptive changes in the media ecosystem caused by convergence and digitization, and analyses innovation processes in content production, distribution and commercialisation. It has been edited by Professors José Miguel Túñez-López (Universidade de Santiago de Compostela, Spain), Valentín-Alejandro Martínez-Fernández (Universidade da Coruña, Spain), Xosé López-García (Universidade de Santiago de Compostela, Spain), José Rúas-Araújo (Universidade de Vigo, Spain) and Francisco Campos-Freire (Universidade de Santiago de Compostela, Spain). The book includes contributions from European and American experts, who offer their views on the audiovisual sector, journalism and cyberjournalism, corporate and institutional communication, and education. It particularly highlights the role of new technologies, the Internet and social media, including the ethics and legal dimensions. With 30 contributions, grouped into diverse chapters, on information preferences and uses in journalism, as well as public audiovisual policies in the European Union, related to governance, funding, accountability, innovation, quality and public service, it provides a reliable media resource and presents lines of future development.
Introduction -- Television and audiovisual sector -- Journalism and cyberjournalism -- Corporate and institutional communication -- Education -- Conclusion.
Keywords: Telecommunication; Multimedia systems; Communication; Advertising media planning; Information technology -- Law and legislation; Mass media -- Law and legislation; Communications Engineering, Networks; Multimedia Information Systems; Media and Communication; Media Planning; IT Law, Media Law, Intellectual Property